Differences in surface chemistry of iron oxide nanoparticles result in different routes of internalization - Svitkova, Barbora; Zavisova, Vlasta; Nemethova, Veronika; Koneracka, Martina; Kretova, Miroslava; Razga, Filip; Ursinyova, Monika; Gabelova, Alena (Beilstein Journal of Nanotechnology, 2021)
The efficient entry of nanotechnology-based pharmaceuticals into target cells is highly desired to reach high therapeutic efficiency while minimizing the side effects. Despite intensive research, the impact of the surface coating on the mechanism of nanoparticle uptake is not sufficiently understood yet. Herein, we present a mechanistic study of cellular internalization pathways of two magnetic iron oxide nanoparticles (MNPs) differing in surface chemistry into A549 cells. The MNP uptake was investigated in the presence of different inhibitors of endocytosis and monitored by spectroscopic and imaging techniques. The results revealed that the route of MNP entry into cells strongly depends on the surface chemistry of the MNPs. While serum bovine albumin-coated MNPs entered the cells via clathrin-mediated endocytosis (CME), caveolin-mediated endocytosis (CavME) or lipid rafts were preferentially involved in the internalization of polyethylene glycol-coated MNPs. Our data indicate that surface engineering can contribute to an enhanced delivery efficiency of nanoparticles.
Keywords: bovine serum albumin; cellular uptake; magnetic iron oxide nanoparticles; polyethylene glycol; surface coating